KAJIAN UJI MEKANISME LIMBAH PLASTIK TIPE 2 (HDPE) UNTUK ZONA LAMBUNG KAPAL DENGAN PENAMBAHAN SERBUK CANGKANG TELUR - Noorohmah (2021)
According to KLHK (2016), Indonesia produces 9.85 billion sheets of plastic bags each year. Barrels from 90 thousand modern deadbolts produce plastic waste, which takes about 20 to 500 years to decompose. And if left unchecked, it concludes nature (the financial ministry of the republic of Indonesia, 2019). One is to reduce plastic waste with the innovation of type 2 plastic waste (hdpe) as another function. One that innovates in the use of plastic waste is Turkey that USES type 2 plastics (hdpe) as shipbuilding materials. Because, plastic type 2 (hdpe) has both durable and resilient characteristics of corrosion roughly 50 years to decompose, has slight rift power that reduces damage, and its high flexibility makes it ideal for ocean weather, and plastic is recyclable. To add powdered eggs with a composition of 97% of calcium carbonate. To generate maximum power, the testing of pulses, the bending test, and the impact test. And for testing the writer made the specimen first using hand lay-up methods according to bki's standards. The results of testing with a variety of hdpe with duck eggshell filings: 97.5% : 2.5%, 2.5% : 7.5% and 90%:10% produce attraction in specimens 90%:10% by 27,532 mpa in the bending test produce bending power of 52.254 mpa and in the im test.